Implementasi Model Pembelajaran Take and Give Pada Mata Pelajaran IPS Kelas V Di MI Ar-Rahim Arjasa - Zainudin, Agus (EDUCARE: Journal of Primary Education, 2021)
This research is the result of research that describes the implementation of the Take and Give learning model in the fifth grade social studies subject at MI Ar-Rahim, Arjasa, Jember. The learning process includes 3 stages, namely the planning, implementation, and evaluation stages. This research aims to answer. Based on the background described above, the formulation of the problems in this study are: 1. How is the preparation in implementing the Take and learning model for class V social studies subjects at MI Ar-Rahim, Arjasa District, Jember Regency? 2. What is the process of implementing the Take and Give learning model for the fifth grade social studies subject at MI Ar-Rahim, Arjasa District, Jember Regency? 3. How is the evaluation in implementing the Take and Give learning model for the fifth grade social studies subject at MI Ar-Rahim, Arjasa District, Jember Regency? The research method used is descriptive qualitative with data collection techniques using observation, interviews and documentation. The data sources in this study were the Principal, Teachers and Grade V Students of Class V Social Studies at MI Ar-Rahim, and other supporting documents. The results of this study indicate: 1. The implementation of the Take and Give learning model in the preparation stage has fulfilled all preparations well. 2. The process of implementing learning in class makes the learning atmosphere fun and students become more active. 3. At the evaluation stage all students have reached the assessment criteria in 3 aspects of the assessment, namely attitudes, knowledge and skills Keywords:Learning model; Take and Give; Social studies lessons Penelitian ini adalah hasil penelitian yang menggambarkan tentang implementasi model pembelajaran Take and Give pada mata pelajaran IPS kelas V di MI Ar-Rahim Kecamatan Arjasa Kabupaten Jember. Proses pembelajaran tersebut meliputi 3 tahap, yaitu tahap perencanaan, pelaksanaan, dan evaluasi. Adapun penelitian ini bertujuan untuk menjawab Berdasarkan latar belakang yang telah dipaparkan di atas, maka rumusan masalah dalam penelitian ini adalah: 1. Bagaimana persiapan dalam mengimplementasikan model pembelajaran Take and mata pelajaran IPS kelas V di MI Ar-Rahim Kecamatan Arjasa Kabupaten Jember? 2. Bagaimana proses dalam implementasi model pembelajaran Take and Givemata pelajaran IPS kelas V di MI Ar-Rahim Kecamatan Arjasa Kabupaten Jember? 3. Bagaimana evaluasi dalam mengimplementasikan model pembelajaran Take and Givemata pelajaran IPS kelas V di MI Ar-Rahim Kecamatan Arjasa Kabupaten Jember? Metode penelitian yang digunakan adalah kualitatif deskriptif dengan teknik pengumpulan data menggunakan observasi, wawancara dan dokumentasi. Adapun sumber data dalam penelitian ini adalah Kepala Sekolah, Guru dan Peserta didik kelas V mata pelajaran IPS kelas V di MI Ar-Rahim, dan dokumen penunjang lainnya. Hasil penelitian inimenunjukkan: 1. Implementasi model pembelajaran Take and Give pada tahap persiapan sudah memenuhi segala persiapan dengan baik. 2. Proses pelaksanaan pembelajaran dikelas membuat suasana belajar menjadi menyenangkan dan peserta didik menjadi lebih aktif. 3. Pada tahap evaluasi semua peserta didik telah mencapai kriteria penilaian dalam 3 aspek penilaian yaitu sikap, pengetahuan dan keterampilan. KataKunci: Model Pembelajaran; Take and Give; Pelajaran IPS